Smallholder farmer perceptions about the impact of COVID-19 on agriculture and livelihoods in Senegal. (May 2021) - Middendorf, B. Jan; Faye, Aliou; Middendorf, Gerad; Stewart, Zachary P.; Jha, Prakash K.; Prasad, P.V. Vara
Abstract: CONTEXT: The global COVID-19 pandemic has produced a variety of unanticipated shocks to farming and socio-economic systems around the world. In case of Senegal, the country was already facing number of challenges at the inception of the pandemic, including high rates of poverty, prevalence of food insecurity, combined with other biophysical and socioeconomic challenges faced generally in Sub-Saharan Africa. OBJECTIVE: To understand farmer perceptions of the potential impacts of COVID-19 on agricultural systems and social well-being of smallholder farmers in Senegal. Particular attention was given to potential vulnerabilities and resilience in the targeted farming systems. METHODS: A survey was developed to better understand smallholder farmer perceptions regarding the anticipated impacts of COVID-19 on their agriculture practices and social well-being. The survey was administered (between June 5 and June 20) with smallholder farmers ( n  = 872) in 14 regions covering all agroecological zones. Variables of interest included perceptions of potential impact on farming systems, agricultural productivity, communities, economics, markets, labor, gendered division of labor, food security, and community well-being. RESULTS AND CONCLUSIONS: Across the three farming systems examined (cropping, livestock, and horticulture) significant majorities expressed concerns related to access to inputs, ability to plant (cropping, horticulture), reduction of yields (cropping, horticulture), ability to feed livestock, ability to sell livestock, and the ability to hire labor (horticulture). The majority of respondents also expressed concern that COVID-19 would make it more difficult to get enough food on a regular basis for their household (82.5%); that the markets where they purchase food will either be closed or significantly disrupted (79.5%); that the price of food would increase (73.5%); and the market where they sell their produce/livestock will be either closed or significantly disrupted (73.2%). SIGNIFICANCE: Anticipated impacts of COVID-19 on agriculture will be felt on both the biophysical aspects such as production and access to inputs and socioeconomic aspects such as access to labor, markets, or rapid shifts in demand. Results support the need to use farming systems approach to gather perceived and actual impacts of COVID-19 and warrants a more in-depth examination of agronomic and biophysical issues as well as the impact on the livelihoods and social well-being of families at community and household levels. Further examination will help identify the characteristics that strengthen smallholder farming systems resilience to adjust to anticipated and unanticipated shocks, such as COVID-19, to decrease the negative impacts and increase the rate of recovery. Graphical abstract: Unlabelled Image Highlights: Farmers perceptions on impact of COVID-19 on food systems in Senegal was quantified. Respondents included 872 farmers from 14 regions across all agroecological regions. Inputs, planting and yields of crops, managing livestock, labor were key concerns. Disruption and access to market for selling and purchasing food is expected. Food availability on a regular basis for their household will be major problem.